The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1088/1748-9326/5/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of forest fires in Scots pine stands of Tuva, Russia

Abstract: Forest fires resulting from long periods of drought cause extensive forest ecosystem destruction and can impact on the carbon balance and air quality and feed back to the climate system, regionally and globally. Past fire frequency is reconstructed for Tuvan Scots pine stands using dendrochronology and statistics. Central Tuvan Scots pine (Pinus sylvestris) stands are subject to annual fire regimes; however high intensity fires are rare but they are responsible for most of the damage. Low, medium, and high sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
8
35
0
Order By: Relevance
“…More frequent forest fires in the boreal forest may have been caused as a result of recent global warming and drier conditions associated with the global change (Soja et al, 2007). The dominant vegetations of boreal forest in Siberia are characterized by larch, pine, spruce and fir (Ivanova et al, 2010). Dehydroabietic acid did not show a peak in the years when levoglucosan showed sporadic peaks although a simultaneous peak was observed in 1949 for two biomass burning tracers (Fig.…”
Section: Dehydroabietic Acid (Pyrolysis Product Of Conifer Resin)mentioning
confidence: 94%
See 1 more Smart Citation
“…More frequent forest fires in the boreal forest may have been caused as a result of recent global warming and drier conditions associated with the global change (Soja et al, 2007). The dominant vegetations of boreal forest in Siberia are characterized by larch, pine, spruce and fir (Ivanova et al, 2010). Dehydroabietic acid did not show a peak in the years when levoglucosan showed sporadic peaks although a simultaneous peak was observed in 1949 for two biomass burning tracers (Fig.…”
Section: Dehydroabietic Acid (Pyrolysis Product Of Conifer Resin)mentioning
confidence: 94%
“…These events may have been caused by forest fires in Siberia because the sampling site is located downwind of Siberia (see Fig. 1), in which boreal forest fires are frequently occurring in spring, summer and autumn (Ivanova et al, 2010). In particular, the enhanced concentration of levoglucosan in the ice core around 1949 suggest enormous fire must have occurred at around that time, although there is no reported peak of forest fires at around 1949 in the southern Siberia ice core (Eichler et al, 2011).…”
Section: Total Organic Carbonmentioning
confidence: 99%
“…Ivanova et al (2010) have shown that extant climate change in combination with socioeconomic changes ($5 time decrease of the forest guard and substantial reduction of firefighting funds over the country during the last 15 years) has resulted in an increase in fire severity and area burned (but not fire frequency) in the Tuva region in southern Siberia. Moreover, the large forest fires that occurred in 2010 were due not only to unusual meteorological conditions but also to poor forest governance and management and an increasing area of abandoned farmlands leading to declining numbers of forest managers, forest firefighters, and less-efficient forest protection systems (Isaev andKorovin, 2014 andFlannigan et al, 2009).…”
mentioning
confidence: 99%
“…The Republic of Tyva (Rus: Respublika Tyva, area 169,000 km^2, Ivanova et al 2010) is one of 83 Federal subjects within the Russian Federation.…”
Section: Tyvamentioning
confidence: 99%
“…At the geographical center of the Asian continent, Tyva experiences a continental climate, with large daily and seasonal ranges of temperatures (Ivanova et al 2010). The population of Tyva is 307,925, 36 % of whom live in the capital Kyzyl Raionov Krainego Severa), a characterization based upon its extreme ecological and climatic conditions and difficulty of access, which lead to high costs of providing for the basic needs of the population.…”
Section: Tyvamentioning
confidence: 99%